(untitled) (Revista Direito em Debate, 2024)
The scope of the present work is studying the corporate investigations as a compliance mechanism of the collective entities, and to analyze the possible application of the regulation about the preservation of the chain of custody to this environment. To this end, it intends to do notes on the institute of compliance and corporate investigations, in addition to going through the rules for the preservation of the chain of custody contained in the Code of Criminal Procedure, and established by 13.964/2019 Law, the so-called Anti-Crime Package. Finally, the aim is to reflect on the applicability of the preservation rules about preserving the chain of custody to the corporate environment, and, if applicable, to analyze any benefits arising therefrom, both to the collective entity and to the State, the main interested party in the solution of crimes. Bibliographical, legislative and jurispruential research methodology was used.